A systematic review of presacral extramedullary haematopoiesis: a diagnosis to be considered for presacral masses. (3rd November 2016) - Zhou, P. P.; Clark, E.; Kapadia, M. R.
Abstract: Aim: Presacral masses are uncommon and have malignant potential; treatment typically includes surgical excision. However, there are conditions such as extramedullary haematopoiesis (EMH) which are benign. The present study aimed to summarize the presentation of presacral EMH in our institution, to review the literature and to offer management strategies for this rare condition. Method: The literature was searched for articles related to presacral EMH, and case reports were collected from articles meeting the inclusion criteria. We collected data on patient demographics, diagnostic investigation, management and the results of treatment. Results: Thirty‐nine patients were included in the systematic review. Initial imaging included computed tomography (CT), magnetic resonance imaging (MRI) or ultrasound (US) suggestive of EMH. Some patients then underwent a technetium scan ( n = 7, 18%), biopsy of the presacral lesion ( n = 27, 69%) or excision of the entire mass ( n = 3, 8%). All patients who underwent technetium scan were confirmed to have EMH, demonstrating enhancement similar to bone marrow. Patients who underwent technetium scan and presacral mass biopsy had concordant results confirming presacral EMH ( n = 5, 13%). Data on management were available for 35/39 (90%) with most patients followed by clinical observation ( n = 20, 51%). Symptomatic patients were treated with radiotherapy (15%), surgical excision (15%) or hydroxyurea (5%) and blood transfusions (10%). Most (81%, n = 17/21) patients whose outcome was reported remained asymptomatic or experienced pain relief. Conclusion: Although uncommon, EMH should be considered in the differential diagnosis of a presacral mass. Presacral EMH is a benign condition that can be suspected on CT or MRI and confirmed with technetium scan. Patients may not necessarily need to undergo biopsy to confirm haematopoietic elements. Unlike other presacral masses, patients diagnosed with presacral EMH can be managed by observation. If symptomatic, radiotherapy or surgical excision may be offered.